The Emerging Evidence Supporting Integration of Deep Regional Hyperthermia With Chemoradiation in Bladder Cancer - Ott, Oliver; Gaipl, Udo; Lamrani, Allison; Fietkau, Rainer (Seminars in Radiation Oncology, 2023)
For decades, the antineoplastic potential of hyperthermia alone or in combination with radiotherapy and/or chemotherapy has been subject of intensive preclinical and clinical research in various tumor entities. The clinical evidence on the beneficial effects of additional hyperthermia in combination with intravesical Mitomycin C for superficial non-muscle-invasive bladder cancer as well as for deep regional microwave hyperthermia techniques applied during an external beam radiotherapy or chemoradiation treatment for more advanced tumors are summarized. In some series, deep regional hyperthermia in combination with an initial transurethral resection and Cisplatin-based chemoradiation increased the 5-year overall survival rates up to 20%. The presented data justifies a fresh irrespective chance for mild regional hyperthermia in the context of new progressive prospective trials on multimodality treatment for bladder preservation.
CRIS-Team Scopus Importer:2022-12-23